Comparison of IDH and ATRX by immunohistochemistry with 1p/19q co-deletion by FISH in Oligodendrogliomas - Hussain, Zahoor; Syed Salman Ali; Sumaira Ilyas; Qurat Ul Ain Mati; Sidra Shoukat; Sawera Ilyas (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine 1p/19q co-deletion by Fluorescence in situ hybridization (FISH) based on positive expression of IDH and ATRX by immunohistochemistry (IHC) in oligodendrogliomas.Study Design: Cross-sectional study.Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Oct 2021 to Jun 2022.Methodology: A total of 58 cases of oligodendrogliomas having positive expression of IDH and ATRX were subjected to FISH for 1p/19q co-deletion. FISH results were correlated with clinicopathological parameters and IHC by using computer software SPSS version 23.Results: In this study, age range is from 14 to 79 years, with mean of 40 years. 30(52%) cases are 0.05). Sensitivity & diagnostic accuracy of IHC with FISH as gold standard showed that combined sensitivity of IDH and ATRX was 100% with diagnostic accuracy of 87.93% for oligodendrogliomas.Conclusion: It’s concluded that oligodendrogliomas can be diagnosed with combined positive expression of IDH and ATRX with sensitivity of 100% and diagnostic accuracy of 87.93% where FISH for 1p/19q co-deletion is not available.